PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOUR SEBAGAI VARIABEL INTERVENING - ASTRINING SARI, SUCCY (Jurnal Ilmu Manajemen (JIM), 2016)
Abstract This study aimed to analyze The Influence Of Organizational Culture On Employees Performance Through Organizational Citizenship Behavior as Intervening Variable . The sample used in this study around 87 employees, that is all employees of the Bank Rakyat Indonesia Blitar Office. However, from 87 sample of employees, only 74 Returned. The data analyze technique used in the study is Structural Equation Model. Partial Least Square with the help of Smart PLS 3.0 Software. The results of this study show that organizational culture has a positive and significant effect on employee performance. organizational culture has a positive and significant effect on Organizational Citizenship Behaviour. Organizational Citizenship Behaviour has a positive and significant on employee performance and No significant influence of organizational culture on employee performance through Organizational Citizenship Behaviour as an intervening variable. Keywords: organizational culture, organizational citizenship behavior, and employee performance. Abstrak Karyawan Melalui Organizational Citizenship Behavior sebagai Intervensi Variabel. Sampel yang digunakan dalam penelitian ini sekitar 87 karyawan, yang seluruh karyawan Kantor Blitar Bank Rakyat Indonesia. Namun, dari 87 sampel karyawan, hanya 74 kembali. Data Teknik analisis yang digunakan dalam penelitian ini adalah Structural Equation Model. Partial Least Square dengan bantuan Smart PLS 3.0 Software. Hasil penelitian ini menunjukkan bahwa budaya organisasi berpengaruh positif dan signifikan terhadap kinerja karyawan. budaya organisasi berpengaruh positif dan signifikan terhadap Organizational Citizenship Behaviour. Organizational Citizenship Behaviour memiliki positif dan signifikan terhadap kinerja karyawan dan ada pengaruh signifikan dari budaya organisasi terhadap kinerja karyawan melalui Organizational Citizenship Behaviour sebagai variabel intervening. Kata kunci: budaya organisasi, perilaku warga organisasi, dan kinerja karyawan.